The research of Hilbert R-Tree spatial index algorithm based on hybrid clustering - Shaohui Zhang; Zhanwei Chen (2011 International Conference on Electronic and Mechanical Engineering and Information Technology, 2011)
In this paper, the R-Tree spatial index structure was analyzed. There are overlap between brother nodes and multi-path in search, which can not effectively reduced by Hilbert R-Tree. Based on hybrid spatial clustering algorithm, a spatial index algorithm is proposed. Experiments show that the algorithm has the faster response speed and the higher query efficiency.